Hypofractionated chemoradiation for head and cancer: Data from the PET NECK trial. (February 2021) - Vreugdenhil, M.; Fong, Charles; Sanghera, Paul; Hartley, Andrew; Dunn, Janet; Mehanna, Hisham
Highlights: There has been a resurgence in interest in hypofractionated chemoradiation due to the pandemic. Hypofractionation chemoradiation was used in the PET neck study. No difference in efficacy or quality of life was seen with hypofractionated chemoradiation. Abstract: There has been increased interest in hypofractionated accelerated chemoradiation for head and neck cancer during the recent first peak of the COVID-19 pandemic. Prospective data regarding this approach from randomised trials is lacking. In the PET NECK study, 564 patients with squamous cell carcinoma of the head and neck receiving definitive chemoradiation were randomised to either planned neck dissection or PET CT scan guided surveillance. In this surgical trial, three radiotherapy fractionation schedules delivered over 7, 6 or 4 weeks were permitted with synchronous chemotherapy. The purpose of this study was to determine efficacy and quality of life outcomes associated with the use of these schedules. Primary local control and overall survival in addition to quality of life measures at immediately post treatment and 6, 12 and 24 months post-treatment were compared between the three fractionation cohorts. In the 525 patients where fractionation data was available, 181 (34%), 288 (55%) and 56 (11%) patients received 68–70 Gy in 34–35 fractions (#), 60–66 Gy in 30# and 55 Gy in 20# respectively. At a minimum follow up of two years following treatment there was no significant difference between the three fractionation schemes in local control, overall survival or any quality of life measure. Despite the obvious limitations of this study, some data is provided to support the use of hypofractionated accelerated chemoradiation to avoid delays in cancer treatment and reduce hospital visits during the peak of a pandemic. Data from on-going randomised trials examining hypofractionated chemoradiation may be useful for selecting fractionation schedules during future pandemics.